Morphological and Structural Evolution of Co3O4 Nanoparticles Revealed by in Situ Electrochemical Transmission Electron Microscopy during Electrocatalytic Water Oxidation - Ortiz Peña, Nathaly; Ihiawakrim, Dris; Han, Madeleine; Lassalle-Kaiser, Benedikt; Carenco, Sophie; Sanchez, Clément; Laberty-Robert, Christel; Portehault, David; Ersen, Ovidiu (ACS nano, 2019)
Unveiling the mechanism of electrocatalytic processes is fundamental for the search of more efficient and stable electrode materials for clean energy conversion devices. Although several in situ techniques are now available to track structural changes during electrocatalysis, especially of water oxidation, a direct observation, in real space, of morphological changes of nanostructured electrocatalysts is missing. Herein, we implement an in situ electrochemical Transmission Electron Microscopy (in situ EC-TEM) methodology for studying electrocatalysts of the oxygen evolution reaction (OER) during operation, by using model cobalt oxide Co3O4 nanoparticles. The observation conditions were optimized to mimic standard electrochemistry experiments in a regular electrochemical cell, allowing cyclic voltammetry and chronopotentiometry to be performed in similar conditions in situ and ex situ. This in situ EC-TEM method enables us to observe the chemical, morphological, and structural evolutions occurring in the initial nanoparticle-based electrode exposed to different aqueous electrolytes and under OER conditions. The results show that surface amorphization occurs, yielding a nanometric cobalt (oxyhydr)oxide-like phase during OER. This process is irreversible and occurs to an extent that has not been described before. Furthermore, we show that the pH and counterions of the electrolytes impact this restructuration, shedding light on the materials properties in neutral phosphate electrolytes. In addition to the structural changes followed in situ during the electrochemical measurements, this study demonstrates that it is possible to rely on in situ electrochemical TEM to reveal processes in electrocatalysts while preserving a good correlation with ex situ regular electrochemistry.